First‐Principles Density Functional Theory and Machine Learning Technique for the Prediction of Water Adsorption Site on PtPd‐Based High‐Entropy‐Alloy Catalysts. Issue 4 (12th February 2023) - Rittiruam, Meena; Setasuban, Sorawee; Noppakhun, Jakapob; Saelee, Tinnakorn; Ektarawong, Annop; Aumnongpho, Nuttanon; Boonchuay, Suphawich; Khajondetchairit, Patcharaporn; Praserthdam, Supareak; Alling, Björn; Praserthdam, Piyasan
Abstract: The water‐gas shift reaction (WGSR) is employed in industry to obtain high‐purity H2 from syngas, where H2 O adsorption is an important step that controls H2 O dissociation in WGSR. Therefore, exploring catalysts exhibiting strong H2 O adsorption energy ( E ads ) is crucial. Also, high‐entropy alloys (HEA) are promising materials utilized as catalysts, including in WGSR. The PtPd‐based HEA catalysts are explored via density functional theory (DFT) and Gaussian process regression. The input features are based on the microstructure data and electronic properties: d‐band center ( ε d ) and Bader net atomic charge ( δ ). The DFT calculation reveals that the ε d and δ of each active site of all HEA surfaces are broadly scattered, indicating that the electronic properties of each atom on HEA are non‐uniform and influenced by neighboring atoms. The strong H2 O‐active‐site interaction determined by a highly negative E ads is used as a criterion to explore good PtPd‐based WGSR catalyst candidates. As a result, the potential candidates are found to have Co, Ru, and Fe as an H2 O adsorption site with Ag as a neighboring atom, that is, PtPdRhAgCo, PtPdRuAgCo, PtPdRhAgFe, and PtPdRuAgFe. Abstract : This work explored 56 systems of PtPd‐based HEA catalysts for water‐gas shift reaction via density functional theory and Gaussian‐process‐regression machine learning. The highly negative adsorption energy is used as a criterion to explore good catalyst candidates. As a result, potential candidates are found to have Co, Ru, and Fe as an H2O adsorption site with Ag as a neighboring atom.